The Closer you look, the greater the book : Bible proofs - Syme, George S.; Syme, Charlotte U. (Denver : Accent Books, 1976)
Published in 1968 under title: The Scriptures cannot be broken.
Includes indexes.
Keywords: Bible -- Evidences, authority, etc